Future directions for the development of Virtual Reality within an automotive manufacturer - Lawson, Glyn; Salanitri, Davide; Waterfield, Brian (Elsevier, 2016)
Virtual Reality (VR) can reduce time and costs, and lead to increases in quality, in the development of a product. Given the pressure on car companies to reduce time-to-market and to continually improve quality, the automotive industry has championed the use of VR across a number of applications, including design, manufacturing, and training. This paper describes interviews with 11 engineers and employees of allied disciplines from an automotive manufacturer about their current physical and virtual properties and processes. The results guided a review of research findings and scientific advances from the academic literature, which formed the basis of recommendations for future developments of VR technologies and applications. These include: develop a greater range of virtual contexts; use multi-sensory simulation; address perceived differences between virtual and real cars; improve motion capture capabilities; implement networked 3D technology; and use VR for market research.